IMPROVING THE PRODUCTION QUALITY OF PALM KERNELAMIDOPROPYL BETAINE (PKAPB) FROM SPLITTED PALM KERNEL FATTY ACID (SPKFA) - Zahra Nafisa, Adhelya
Coconut oil is the primary raw material used in the production of betaine surfactants or cocamidopropyl betaine (CAPB), which are widely used in cleaning and personal care products. However, Indonesia still imported 15,000 tons of CAPB, valued at 20 million USD, in 2020. One potential raw material that could replace coconut oil in surfactant production is palm kernel oil. Betaine surfactant derived from palm kernel oil (palm kernelamidopropyl betaine, PKAPB) is produced through two stages of reaction: amidation and carboxymethylation. Currently, PKAPB production is conducted at a laboratory scale and has not yet met the specifications of commercial CAPB products. This research aims to improve the quality of PKAPB surfactants and increase the production scale of PKAPB with a feed of 1.25 kg of splitted palm kernel fatty acid (SPKFA) per batch. PKAPB production was conducted in duplicate at a laboratory scale with variations in the amidation reaction, namely nitrogen flow rates (in ml/min) of 25; 50; 75; 100; 150; 200; no nitrogen; and nitrogen flushing at the beginning of the reaction at a rate of 100 ml/min for 15 minutes, as well as variations in the amount of make-up dimethylaminopropyl amine (DMAPA) during the amidation reaction of 0%; 15%; 30%; and 45%. PKAPB analysis parameters included active ingredient content, acid number, viscosity, product color, pH, density, NaCl content, and water content. The experimental results showed that increasing the nitrogen flow rate up to 100 ml/min and adding at least 30% DMAPA during the amidation reaction could improve the quality of PKAPB. The combination of a nitrogen flow rate of 75 ml/min and 45% DMAPA on a semi-pilot scale produced PKAPB surfactants that closely approached commercial CAPB specifications, although further adjustments were needed for product color and viscosity.